Characteristics of patient communication and prevalence of communication difficulty in the intensive care unit: An observational study. Issue 5 (September 2019) - Freeman-Sanderson, Amy; Morris, Katherine; Elkins, Mark
Abstract: Purpose: To summarise the patient communication status in an intensive care unit (ICU), including methods of communication used and the frequency, degree and nature of communication breakdown. Materials and methods: A multidisciplinary daily ward audit was conducted on ten consecutive weekdays in a 30-bed general ICU of a tertiary Australian hospital. Data included patient demographics, patients' mode of communication and the level of difficulty in communicating. Descriptive statistics and means (standard deviation)/medians (interquartile range) were used to summarise the data. Results: Over the audit period, data were collected from 87 patients (median age 58 years, interquartile range 43 to 67; 60% males), equivalent to 232 occupied bed days. Patients from non–English-speaking backgrounds accounted for 14% of the cohort, with Mandarin the most common non-English language. Altered cognition occurred on 11% of bed days. Staff reported difficulty in communicating with patients on 35% of bed days, with an inability to communicate with patients in 49% of these cases. Alternate modes of communication were reported, with gesture the most common, but they were not used with all suitable patients. Conclusions: About one-third of the caseload in the ICU experienced difficulty in communicating. While alternate communication methods were reported, they were not used with all patients. A multidisciplinary approach to enhance communication ability may be beneficial.